PGAP2-Related Hyperphosphatasia-Mental Retardation Syndrome: Report of a Novel Patient, Toward a Broadening of Phenotypic Spectrum and Therapeutic Perspectives - Saracino, Annalisa; Totaro, Martina; Politano, Davide; DE Giorgis, Valentina; Gana, Simone; Papalia, Grazia; Pichiecchio, Anna; Plumari, Massimo; Rognone, Elisa; Varesio, Costanza; Orcesi, Simona (Neuropediatrics, 2024)
PGAP2 gene has been known to be the cause of “hyperphosphatasia, mental retardation syndrome-3” (HPMRS3). To date, 14 pathogenic variants in PGAP2 have been identified as the cause of this syndrome in 24 patients described in single-case reports or small clinical series with pan-ethnic distribution. We aim to present a pediatric PGAP2-mutated case, intending to further expand the clinical phenotype of the syndrome and to report our experience on a therapeutic approach to drug-resistant epilepsy.We present the clinical, neuroradiological, and genetic characterization of a Caucasian pediatric subject with biallelic pathogenic variants in the PGAP2 gene revealed by next generation sequencing analysis.We identified a subject who presented with global developmental delay and visual impairment. Brain magnetic resonance imaging showed mild hypoplasia of the inferior cerebellar vermis and corpus callosum and mild white matter reduction. Laboratory investigations detected an increase in alkaline phosphatase. At the age of 13 months, he began to present epileptic focal seizures with impaired awareness, which did not respond to various antiseizure medications. Electroencephalogram (EEG) showed progressive background activity disorganization and multifocal epileptic abnormalities. Treatment with high-dose pyridoxine showed partial benefit, but the persistence of seizures and the lack of EEG amelioration prompted us to introduce ketogenic diet treatment.Our case provides a further phenotypical expansion of HPMRS3 to include developmental and epileptic encephalopathy. Due to the limited number of patients reported so far, the full delineation of the clinical spectrum of HPMRS3 and indications for precision medicine would benefit from the description of new cases and their follow-up evaluations.
Keywords: developmental and epileptic encephalopathy; glycosylphosphatidylinositol (GPI)-anchor biosynthesis; pyridoxine; ketogenic diet